Perancangan Sirkulasi Koridor Klinik Fisioterapi untuk Optimalisasi Aksesibilitas Difabel - Hilda Aulia Setiawan; Adisti Ananda Yusuff (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Physiotherapy clinics serve patients with varying levels of mobility, including people with disabilities, so corridor circulation must be designed to be accessible and efficient. This study aims to identify the existing condition of corridor circulation in physiotherapy clinics in South Jakarta, analyze its compliance with accessibility standards for people with disabilities, and formulate design recommendations. The method used is a qualitative approach with Evidence-Based Design through observation, informal interviews, and documentation. The results show that the corridor width does not meet the standard for two-way circulation for wheelchair users, there is no maneuvering area at the door opening, and there are minimal elements supporting safety and spatial orientation. Based on anthropometric analysis and universal design principles, it is recommended to improve corridor dimensions and provide maneuvering space. These recommendations are expected to improve circulation efficiency, safety, and comfort for physiotherapy clinic users.